Strength-ductility synergy in dissimilar friction stir welded Al-Cu joints via introducing pin eccentricity - Hou, Wentao; Hu, Yongsheng; Qiang, Fei; Shen, Zhikang; Chen, Jianbin; Li, Junping; Huda, Nazmul; Luqman Hakim, Ahmad Shah; Shen, Yifu (Elsevier, 2025)
In dissimilar friction stir welding (FSW) joints, the stir zone, where brittle IMCs are extensively distributed, is usually the origin of crack initiation, which can severely deteriorate the joint performance. To improve the mechanical properties of Al-Cu friction stir weld joints by optimizing the stir zone microstructure and the distribution of IMCs particles, an eccentric welding tool was adopted to perform dissimilar friction stir welding of Al alloy to commercially pure Cu. Microstructure evolution of the stir zone was investigated by varying the value of pin eccentricity ranging from 0 to 0.4 mm using scanning electron microscopy (SEM), X-ray spectroscopy (EDS), optical microscopy (OM) and transmission electron microscopy (TEM). Mechanical properties, including ultimate tensile strength and elongation, of the samples produced with different eccentricity were evaluated by means of quasi-static uniaxial tensile test. The results indicate that with the application of pin eccentricity, a strength-ductility synergy was achieved, where the joint ultimate tensile strength (UTS) increased by 32 % to ~198 MPa with 0.4 mm eccentricity from ~150 MPa without pin eccentricity, and the corresponding elongation of the Al-Cu joints was also significantly increased, reaching up to 10.3 %. The enhanced strength-ductility synergy observed in the joints can be attributed to the significant refinement and more uniform distribution of Cu and intermetallic compound (IMC) particles within the stir zone, facilitated by the intensified straining effect of the eccentric pin. This study presents a novel approach for the fabrication of Al-Cu dissimilar joints that achieves superior strength while maintaining satisfactory ductility, thereby offering a balanced solution for the improvement of joint performance.